Low-molecular-weight anti-HIV-1 agents targeting HIV-1 capsid proteins - Kobayakawa, Takuya; Yokoyama, Masaru; Tsuji, Kohei; Fujino, Masayuki; Kurakami, Masaki; Onishi, Takato; Boku, Sayaka; Ishii, Takahiro; Miura, Yutaro; Shinohara, Kouki; Kishihara, Yuki; Ohashi, Nami; et al. (RSC advances, 2023)
The HIV-1 capsid is a shell that encapsulates viral RNA, and forms a conical structure by assembling oligomers of capsid (CA) proteins. Since the CA proteins are highly conserved among many strains of HIV-1, the inhibition of the CA function could be an appropriate goal for suppression of HIV-1 replication, but to date, no drug targeting CA has been developed. Hydrophobic interactions between two CA molecules through Trp184 and Met185 in the protein are known to be indispensable for conformational stabilization of the CA multimer. In our previous study, a small molecule designed by in silico screening as a dipeptide mimic of Trp184 and Met185 in the interaction site was synthesized and found to have significant anti-HIV-1 activity. In the present study, molecules with different scaffolds based on a dipeptide mimic of Trp184 and Met185 have been designed and synthesized. Their significant anti-HIV activity and their advantages compared to the previous compounds were examined. The present results should be useful in the design of novel CA-targeting anti-HIV agents. Design and synthesis of MKN-3 derivatives: a new class of small molecules, MKN-3 derivatives, were developed based on in silico screening, as dipeptide mimics of Trp184 and Met185 at the hydrophobic interaction site between two capsid (CA) proteins.